Globalization and the transmission of social values: The case of tolerance - Niclas Berggren; Therese Nilsson (Research Institute of Industrial Economics (IFN), 2014)
Tolerance - respecting those who are different - is arguably of particular importance in an era of globalization, where a potential for economic, social and personal development is increasingly a function of interaction with others different from oneself. We investigate whether globalization induces parents to want to instill tolerance in their children, the main idea being that this would equip the latter for greater success in a more integrated world. We indeed find, using a willingness-to-teach-kids-tolerance measure, that globalization enhances the willingness to transmit such social values. More precisely, economic and social, but not political, globalization has this effect, as shown by using the KOF Index of Globalization in cross-sectional and panel-data regression analyses of up to 66 countries. Addressing potential endogeneity concerns using an instrumental variables approach moreover suggests these relationships to be causal. Overall, our results confirm that certain kinds of globalization seem able to shape values in ways considered desirable by many.
Keywords: F01; F10; P45; Z13; 330; Globalization; Tolerance; Social values; Children; Welfare state